2022
DOI: 10.1111/febs.16527
|View full text |Cite
|
Sign up to set email alerts
|

New structural insights into the PI‐2 pilus from Streptococcus oralis, an early dental plaque colonizer

Abstract: Streptococcus oralis is a member of the mitis group of oral streptococci and an early colonizer in dental plaque biofilm, a major cause of periodontal disease, dental caries, and other oral infections. S. oralis promotes biofilm growth by coaggregating in a mutualistic partnership with other early colonizers such as Actinomyces oris. For this cell‐to‐cell interaction, A. oris is known to use its sortase‐dependent pilus (type 2), but whether S. oralis uses its PI‐2 (pilus islet 2) pilus is still to be determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…The structure of PitB (PDB ID: 7F7Y), the backbone pilin, has been resolved to 2.8 Å. It is 110 Å long and 40 Å wide and consists of two domains, D1 and D2 ( Figure 2B ), whose covalent binding is catalyzed by the sortase SrtG1 ( Yadav and Krishnan, 2022 ). The two domains of PitB present an irregular structure; the N-terminal D1 domain consists of 12 chains, and the C-terminal D2 domain consists of 11 chains ( Shaik et al., 2015 ).…”
Section: Characteristics and Structure Of The Pilusmentioning
confidence: 99%
“…The structure of PitB (PDB ID: 7F7Y), the backbone pilin, has been resolved to 2.8 Å. It is 110 Å long and 40 Å wide and consists of two domains, D1 and D2 ( Figure 2B ), whose covalent binding is catalyzed by the sortase SrtG1 ( Yadav and Krishnan, 2022 ). The two domains of PitB present an irregular structure; the N-terminal D1 domain consists of 12 chains, and the C-terminal D2 domain consists of 11 chains ( Shaik et al., 2015 ).…”
Section: Characteristics and Structure Of The Pilusmentioning
confidence: 99%
“…49 Recently, a structural model for pneumococcal PI-2 pili was proposed using crystal structure analysis, in which repeating PitB subunits were arranged head-to-tail to form a long backbone structure with PitA on the outer tip (Figure 3). 50 A classic study in 1975 reported that some streptococcal strains isolated from human throats produced spreading zones around colonies on blood agar. 101 These strains were identified as "S. sanguis" (oral mitis group), and the spreading growth was caused by twitching motility.…”
Section: Cell Surface Proteins and Enzymes (2): Pilimentioning
confidence: 99%
“…Recently, a structural model for pneumococcal PI‐2 pili was proposed using crystal structure analysis, in which repeating PitB subunits were arranged head‐to‐tail to form a long backbone structure with PitA on the outer tip (Figure 3). 50 …”
Section: Cell Surface Proteins and Enzymes (2): Pilimentioning
confidence: 99%
“…The structural, functional and molecular properties of streptococcal RPS support a recognition role of these cell surface molecules in oral biofilm formation [16,17]. According to research, the cell wall polysaccharides found in S. oralis and other streptococci of the viridans work together as receptors for lectin-like adhesins located on other components of the oral biofilm community [18].…”
Section: Introductionmentioning
confidence: 99%